Alkalinisation of lignocaine to reduce the pain of digital nerve blockade. Issue 5 (September 1996) - Cornelius, P; Kendall, J; Meek, S; Rajan, R
Abstract : OBJECTIVE: To see if the alkalinisation of lignocaine caused a reduction in the pain of injection for digital nerve blockade. METHODS: The study was a prospective randomised double blind study with each patient acting as their own control. During the study period, all patients aged 16 years and over presenting to the accident and emergency department with a condition requiring digital nerve blockade were considered for inclusion in the study. Each patient received an injection of both alkalinised and non-alkalinised lignocaine. The pain of each injection was then assessed on a visual analogue scale. RESULTS: 98 patients were entered in the study. The mean difference in pain scores between the non-alkalinised and alkalinised injections was 0.739, P < 0.001, 95% confidence interval 0.47 to 1.01. CONCLUSIONS: Alkalinisation of lignocaine reduces the pain of injection for digital nerve blockade.